The finalizing of the commercial agency contract in Islamic jurisprudence and the Saudi system - Alwehaibi, Mansour Abdulaziz Abdullah (Journal of Islamic Sciences, 2022)
The research aimed at clarify the reasons for the termination of the commercial agency and its effects on the principal, the agent and others in Islamic jurisprudence and the Saudi system.The research relies on the inductive and analytical approach, so that the texts of the commercial agency system were extrapolated and what is jurists decided, measure that and then extract what is related to the causes and effects of terminating the commercial agency from its fold, as comparison was made between the Saudi System and Islamic jurisprudence.The topic is divided to preface and two chapters.In the preface, I addressed what is the commercial agency contract.In the first chapter, I addressed the reasons of finalizing the commercial agency contract in doctrine and system.In the second chapter, I adressred the effects of finalizing of the commercial agency contract in doctrine and system, then I mentioning several judicial applications on the finalizing of the commercial agency contract and commenting on them.As for the conclusion: it included the most important results and recommendations reached by the researcher.Among the most important findings of research: The commercial agency is a crisis for the client and agent anf it may not be terminated except for a legitimate justification.
Keywords: commercial agency; termination of contract; agency by commission; contract agency